Transcriptome profiling reveals novel insights into the regulation of calcium ion and detoxification genes driving chlorantraniliprole resistance in Spodoptera exigua - Changhee Han; Juil Kim (Heliyon)
Since the commercialization of diamide insecticides, including chlorantraniliprole, in 2007, the overuse of diamide insecticides for over a decade has resulted in excessive chlorantraniliprole resistance in Spodoptera exigua, causing continuous economic losses. While RyR target-site mutations and detoxification enzymes such as cytochrome P450 have been studied as the leading causes of resistance, previous studies, including functional research and synergistic tests, have not confirmed a clear correlation between these factors and the development of resistance. Thus, transcriptome analysis was employed to investigate alternative strategies beyond mutation(s) in RyR or metabolic factors involving detoxification pathways that allow diamide-resistance S. exigua to counteract the calcium ion imbalances induced by chlorantraniliprole effectively. Diamide-resistant, susceptible strains and its F1-hybrid of S. exigua were used for the RNAseq-based differentially expressed gene (DEG) analysis. In total 4669 genes were differentially expressed, with 2809 upregulated and 1860 downregulated in the resistant strain compared to the susceptible strain. GO, KEGG enrichment and orthologous analyses demonstrated that genes involved in metabolic factors were overrepresented in the resistant strain. In particular, overexpressed endoplasmic reticulum (ER)-related calcium ion homeostasis and cell stability-associated genes were newly identified in resistant strain. The selected differentially expressed genes were validated then with qPCR. These genes were inferred to induce cell stability to overcome ER stress derived from calcium ion imbalance caused by chlorantraniliprole. These results provide advanced insights into the critical roles of calcium ion homeostasis- and cell stability-related genes in conferring diamide insecticide resistance.